Regulation of Cyclooxygenase 2 mRNA Stability by the Mitogen-Activated Protein Kinase p38 Signaling Cascade - Lasa, Marina (American Society for Microbiology, 2000)
A tetracycline-regulated reporter system was used to investigate the regulation of cyclooxygenase 2 (Cox-2) mRNA stability by the mitogen-activated protein kinase (MAPK) p38 signaling cascade. The stable β-globin mRNA was rendered unstable by insertion of the 2,500-nucleotide Cox-2 3′ untranslated region (3′ UTR). The chimeric transcript was stabilized by a constitutively active form of MAPK kinase 6, an activator of p38. This stabilization was blocked by SB203580, an inhibitor of p38, and by two different dominant negative forms of MAPK-activated protein kinase 2 (MAPKAPK-2), a kinase lying downstream of p38. Constitutively active MAPKAPK-2 was also able to stabilize chimeric β-globin–Cox-2 transcripts. The MAPKAPK-2 substrate hsp27 may be involved in stabilization, as β-globin–Cox-2 transcripts were partially stabilized by phosphomimetic mutant forms of hsp27. A short (123-nucleotide) fragment of the Cox-2 3′ UTR was necessary and sufficient for the regulation of mRNA stability by the p38 cascade and interacted with a HeLa protein immunologically related to AU-rich element/poly(U) binding factor 1.